Carboniferous magmatic records of central Mongolia and its implications for the southward subduction of the Mongol–Okhotsk Ocean. Issue 6 (26th March 2023) - Zhu, Mingshuai; Miao, Laicheng; Zhang, Fuqin; Ganbat, Ariuntsetseg; Baatar, Munkhtsengel; Anaad, Chimedtseren; Yang, Shunhu; Wang, Zeli
ABSTRACT: The now-extinct Palaeozoic to Mesozoic Mongol–Okhotsk Ocean is evidenced by the Mongol–Okhotsk suture, which stretches from central Mongolia to the Sea of Okhotsk. The geodynamics of southward subduction of the Mongol–Okhotsk Ocean remain enigmatic, especially whether the subduction began during the Carboniferous is highly debated. In this paper we present new zircon U–Pb ages and whole-rock geochemical data for the Carboniferous magmatic rocks in Northeast Mongolia. Zircon U–Pb dating indicates that the Adaatsag dacite, Northern Bayanjargalan gabbro-diorite and Bagannur pluton were emplaced at ca. 325 Ma, ca. 316 Ma, and ca. 305 Ma, respectively. Occurrences of these rocks together constitute a Carboniferous magmatic belt to the northwest of the Middle Gobi volcanic-plutonic belt. The ages of trapped zircon xenocrysts within the Bagannur pluton indicate that the basement of this magmatic belt is the Ereendavaa terrane. Geochemical analysis indicates that these magmatic rocks were formed in an Andean-type active margin, which provides robust evidence for southward subduction of the Mongol-Okhotsk Ocean during the Late Carboniferous. By combining all the available data, we argue that the onset of the Central Mongolia–Tsagaan Uul continental collision during the Late Carboniferous – Early Permian may have triggered the beginning of an active margin of the Mongol-Okhotsk Ocean along the northern coast of the Central Mongolia microcontinent.